Web System for Online and Onsite Usage of Geoinformation by Surveying Sector in Kosovo. Case Study: Ferizaj Municipality - Bashkim Idrizi; Mirdon Kurteshi (Department of Geography Education, University of Jember, 2019)
The purpose of research to determine and contribute in more efficient services to geoinformation stakeholders, as well as to give positive impact on increasing income in geo business sector, voluntary based web system for online usage of geoinformation in Kosovo has been developed. The method used was puting in to one place many sourcec via WMS and WFS services, by creating thematic SDI, in order to have online system with dynamic data comming from official databases with update from last day on 5 pm. System is open for usage by all interested parts, however official registration is required. It contains geoinformation from many databases such as cadastral, orthophoto, municipal, and basemaps from open layers. The results show that the system is extendable and it is permanently including new datasets based on the user requirements. All available data is linked via web services, which gives an opportunity to users to use the updated version of datasets as they are published by responsible institution via www (world wide web). Keywords: web map, geoportal, geoinformation, web services, Kosovo References Alameh. N, (2010). Service chaining of interoperable Geographic Information Web Services. Global Science and Technology. Greenbelt, USA. Brimicombe, A.J. (2002). GIS-where are the frontiers now. GIS 2002. Bahrain. Bryukhanova, E. A., Krupochkin, Y. P., & Rygalova, M. V. (2018). Geoinformation technologies in the reconstruction of the social space of siberian cities at the turn of the 19–20th centuries (case study of the city of tobolsk). Journal of Siberian Federal University - Humanities and Social Sciences, 11(8), 1229-1242. doi:10.17516/1997-1370-0303 Chaudhuri, S. (2015). Application of Web Based Geographical Information Systems in e-business. Maldives. Davis, C.A. and Alves L.L. (2007). Geospatial web services, Vicosa, Brazil. ESRI. (2003). Spatial Data Standards and GIS interoperability. White paper. ESRI. CA. USA. Ferdousi, . and Al-Faisal, A. (2018). Urban and regional planning. Rajshahi University of Engineering and Technology. Rajshahi. Bangladesh. Gitis, V., Derendyaev, A., & Weinstock, A. (2016). Web-based GIS technologies for monitoring and analysis of spatio-temporal processes. International Journal of Web Information Systems, 12(1), 102-124. doi:10.1108/IJWIS-10-2015-0032 Glasze, G., & Perkins, C. (2015). Social and political dimensions of the OpenStreetMap project: Towards a critical geographical research agenda doi:10.1007/978-3-319-14280-7_8 Henzen, C. (2018). Building a framework of usability patterns for web applications in spatial data infrastructures. ISPRS International Journal of Geo-Information, 7(11) doi:10.3390/ijgi7110446 Idrizi, B. (2009). Developing of National Spatial Data Infrastructure of Macedonia according to global standardization (GSDI and INSPIRE) and local status. Conference of Nikodinovski. Skopje. Macedonia. Idrizi, B. (2018). General Conditions of Spatial Data Infrastructure. International Journal on Natural and Engineering Sciences. Turkey. Idrizi, B. Sulejmani, V. Zimeri, Z. (2018). Multi-scale map for three levels of spatial planning data sets for the municipality of Vitia in Kosova. 7th ICC&GIS conference. Sozopol. Bulgaria. Mwange, C., Mulaku, G. C., & Siriba, D. N. (2018). Reviewing the status of national spatial data infrastructures in africa. Survey Review, 50(360), 191-200. doi:10.1080/00396265.2016.1259720 Nikolov, B. P., Zharkikh, J. I., Soloviev, A. A., Krasnoperov, R. I., & Agayan, S. M. (2015). Integration of data mining methods for earth science data analysis in GIS environment. Russian Journal of Earth Sciences, 15(4) doi:10.2205/2015ES000559 Sahin, K. and Gumusay, M.U. (2008). Service oriented architecture based web services for geographic information systems. The international archives of the remote sensing, photogrammetry and spatial information sciences. Vol XXXVII. Beijing. China. Sayar, A. (2008). GIS service oriented architecture. Community grids laboratory. IN, USA. Shi, S. (2015). Design and development of an online geoinformation service delivery of geospatial models in the united kingdom. Environmental Earth Sciences, 74(10), 7069-7080. doi:10.1007/s12665-015-4243-8 Siles, G., Charland, A., Voirin, Y., & Bénié, G. B. (2019). Integration of landscape and structure indicators into a web-based geoinformation system for assessing wetlands status. Ecological Informatics, 52, 166-176. doi:10.1016/j.ecoinf.2019.05.011 Ummadi, P. (2008). Standards and Interoperability in GIS, Michigan State University. MI, USA. Vorobev, A. V., & Shakirova, G. R. (2016). Web-based geoinformation system for exploring geomagnetic field, its variations and anomalies doi:10.1007/978-3-319-29589-3_2 Walter, V., & Sörgel, U. (2018). Implementation, results, and problems of paid crowd-based geospatial data collection. PFG - Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 86(3-4), 187-197. doi:10.1007/s41064-018-0058-z Copyright (c) 2019 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License